235 Root cause analysis of barriers and facilitators to accrual to a pragmatic, EHR-embedded clinical trial - Lindsay Lennox; Bethany M Kwan; Adit A Ginde; Thomas W. Flaig; Sarah V Kautz; Matthew Mimnall; Andrew Nicklwsky; Goldie Komaie; Christine Velez; Aaron Babour; Laurie Blmberg-Romero; Cecilia C. Low Wang (Journal of Clinical and Translational Science)
Objectives/Goals: Electronic health record (EHR)-based recruitment can facilitate participation in clinical trials, but is not a panacea to trial accrual challenges. We conducted a root cause analysis to identify EHR-based accrual barriers and facilitators in a pragmatic randomized trial of metformin for those with prostate cancer and glucose intolerance. Methods/Study Population: We quantitatively analyzed enrollment drop-offs among eligible patients who either did not complete a consent (with analysis of EHR-embedded consent process) or who completed a consent but were not enrolled (with analysis of EHR implementation of a Best Practice Alert). We summarized data from the EHR by eligibility, provider encounters, and alerts, and generated CONSORT diagrams and tables to trace the enrollment pathway. We supplemented quantitative findings with a thematic analysis of semi-structured individual interviews with eligible patients (n = 10) and study providers (n = 4) to identify systematic barriers to recruitment and enrollment of eligible patients. Results/Anticipated Results: CONSORT diagram analysis found that 24% of potentially eligible patients (268 of 1130) had an eligible study encounter but were not enrolled. Additionally, BPAs were not triggering for some eligible patients. Interviews revealed that study providers wanted more detailed information about which study arm their patient would be assigned to, and about next steps after enrollment, especially relating to additional lab tests and follow-up care needed. Patient interviews suggested that patients often did not remember completing the consent process and felt overwhelmed with appointments and information; patients expected providers to actively bring up research opportunities during appointments. Discussion/Significance of Impact: While pragmatic EHR-embedded trials are often characterized as lower-burden, these trials still require active engagement by providers, as well as ongoing attention from both research and informatics teams to ensure that EHR-embedded processes are functioning as designed, and that they are effective in recruiting study participants.